When stars light the sky [large type] - Camden, Elizabeth, 1965- (Camden, Elizabeth, 1965- Women of Midtown, 2025)
"When duty calls, Inga Klein sails for Berlin to become the secretary for America's ambassador. The ambassador's imposing chief of staff, Benedict Kincaid, mistrusts German-born Inga immediately, but when tragedy strikes and war looms, a marriage of convenience may be Inga's only hope of safety"--